ANALISIS PENINGKATAN KECERDASAN LOGIS MATEMATIS ANAK USIA 4-6 TAHUN MENGGUNAKAN PERMAINAN TRADISIONAL TK GASEH POMA - MULIANA MULIANA (Serambi Tarbawi, 2018)
The research aims to describe the traditional game in development of logical mathematical intelligence to children aged 4-6 years, then what kind of traditional games that can be applied in development of logical-mathematical intelligence to children aged 4-6 years. The research method was descriptive qualitative and quantitative to describe the complete exposure of research results through observation techniques conducted in the field in detail and description related to the development of logical-mathematical intelligence to children aged 4-6 years using traditional games. The data were obtained and conducted in kindergarten institutions it Kuta Alam, Banda Aceh in 2018. The results were obtained: (1) traditional games in development of logical-mathematical intelligence proved effective applied in learning children aged 4-6 Year, (2) traditional game of simbang batu and simbang batu developed logical- mathematical intelligence of children aged 4-6 years. The results of this research as an insight, further research development studies to develop the intelligence of other children and continue to explore various types of traditional games that can be used in early childhood learning